Modified embedded-atom method interatomic potentials for the Nb-C, Nb-N, Fe-Nb-C, and Fe-Nb-N systems - Kim, Hyun-Kyu; Jung, Woo-Sang; Lee, Byeong-Joo (CAMBRIDGE UNIV PRESS, 2010)
Modified embedded-atom method (MEAM) interatomic potentials for Nb-C, Nb-N, Fe-Nb-C, and Fe-Nb-N systems have been developed based on the previously developed MEAM potentials for lower order systems. The potentials reproduce various fundamental physical properties (structural properties, elastic properties, thermal properties, and surface properties) of NbC and NbN, and interfacial energy between bcc Fe and NbC or NbN, in generally good agreement with higher-level calculations or experimental information. The applicability of the present potentials to atomic-level investigations to the precipitation behavior of complex-carbonitrides (Nb,Ti)(C,N) as well as NbC and NbN, and their effects on the mechanical properties of steels are also discussed.
Keywords: TRANSITION-METAL NITRIDES; THERMODYNAMIC ASSESSMENT; GROUP-V; 4D-TRANSITION-METAL CARBIDES; ELECTRONIC-PROPERTIES; ELASTIC-CONSTANTS; CRYSTAL-STRUCTURE; AB-INITIO; TI-C; NIOBIUM